Date Mucilage as Co-Polymer in Metformin-loaded Microbeads for Controlled Release (2019)
The World Health Organization (WHO) has recognized the use of rectal preparations for certain indications in children as an alternative to parenteral. However, challenges of stability in tropical countries have limited its application. Furthermore, adverse effects arise in the use of some excipients in infants and neonates. In this study, paediatric paracetamol suppositories using two plant-derived fats - shea butter and dika fat - and their combination as suppository bases in comparison with cocoa butter were formulated. Shea butter and dika fat were purified and characterised using acid, iodine and saponification values, refractive index and relative density. Paracetamol suppositories were formulated by fusion method and evaluated using appearance, weight uniformity, melting point range, solidification point, crushing strength, disintegration time and dissolution test. Physicochemical properties showed shea butter and dika fat as stable with minimal susceptibility to oxidation with melting point ranges of 32 - 35C and 37 - 39C respectively. Base mixtures yielded melting point ranges of 32 - 39C. The suppositories had crushing strengths  31 N and disintegration times ranged between 3 - 21 min. Paracetamol release from the single bases ranked cocoa butter >dika fat > shea butter. Paediatric paracetamol suppositories using these plant-derived fats compared well with cocoa butter. Paracetamol suppositories with mixtures of either shea butter or dika fat with cocoa butter had superior release properties compared to cocoa butter alone. Thus, could serve as an alternative to cocoa butter in the formulation of suppositories.